2013
DOI: 10.1111/jocn.12433
|View full text |Cite
|
Sign up to set email alerts
|

Let's talk about sex: lower limb amputation, sexual functioning and sexual well‐being: a qualitative study of the partner's perspective

Abstract: Participants in our study reported minor changes in their sexual well-being. Most of them indicated that communication about the changes expected and how to cope with these would have been helpful. It is therefore important that professionals address sexuality during the rehabilitation process with patients and partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…18 Despite this, prosthetists/orthotists do not appear to be addressing sexual health issues with their clients. 20 To change this pattern of behavior, it is necessary to introduce formal training on sexual health care into P&O educational programs. This will first require an understanding of students' current knowledge and perceived needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Despite this, prosthetists/orthotists do not appear to be addressing sexual health issues with their clients. 20 To change this pattern of behavior, it is necessary to introduce formal training on sexual health care into P&O educational programs. This will first require an understanding of students' current knowledge and perceived needs.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who have undergone an amputation have indicated that the development of prostheses and assistive devices to facilitate sexual activity would improve their sexual life. 18 These could include orthoses to facilitate positioning, 19 limb prostheses specifically for sexuality-related reasons, 20 and cosmetic prostheses to enhance a person's perceived body image and attractiveness. 12 There are numerous factors that influence the ability of health professionals to address issues related to sexual health.…”
Section: Boxmentioning
confidence: 99%
“…chemotherapy effects in cancer). These relational changes were deemed to be secondary to focusing on the survival and health of the PWLL (Verschuren et al, 2013). This may again represent a process in which spouses diminish their own needs in order to focus on the PWLL.…”
Section: Lived Experience Of Familiesmentioning
confidence: 99%
“…This reductionist view of the network's experience also arises as the research has so far been limited in its focus to specific issues within limb loss. This includes examining only sexuality (Verschuren et al, 2013); or using an interview schedule based on a previous schedule for PWLL (Thompson & Haran, 1984). With one exception (Livingstone et al, 2011), participants have not been provided with the freedom to determine their own issues of importance.…”
Section: Lived Experience Of Familiesmentioning
confidence: 99%
“…En términos del cansancio sexual, el tránsito de la normalidad a la anormalidad no es menos oneroso: las diversidades anatómicas pronto se transforman en anormalidad, de esta manera hombres y mujeres se sienten en carencia: los penes son percibidos como pequeños 41 y las vulvas como deformes y redundantes 42 . En medio de esta dinámica se suele recurrir a los desarrollos de la tecnociencia como opción para paliar la deficiencia percibida y optimizar el rendimiento.…”
Section: Los Seres Sexuales «Anormales» En Su Normalidadunclassified